2002
DOI: 10.1037/0735-7036.116.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus control of maternal responsiveness to Norway rat ( Rattus norvegicus) pup ultrasonic vocalizations.

Abstract: Mother rats (Rattus norvegicus; 6 to 8 days postpartum) approach and maintain proximal orientation to a pup that is emitting ultrasonic vocalizations (USVs) far more than do virgin females (W. J. Farrell & J. R. Alberts, 2002). We used a playback regimen to examine the roles of acoustic and nonacoustic cues in regulating maternal proximal orientation toward vocalizing pups. When presented with recorded USVs, mothers of 6- to 8-day-old pups and nulliparous virgin females exhibited equivalent levels of proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 22 publications
(70 reference statements)
2
42
1
Order By: Relevance
“…Mother rats (Rattus norvegicus) approach and maintain proximity to a pup that is emitting cries (ultrasonic vocalizations) significantly more than do virgin rats [25]. This study showed that a warm, silent pup together with recorded ultrasounds was required to elicit approach of maternal or virgin females, the former remaining in proximity of the pup for a significantly longer period of time.…”
Section: Crying and Parental Behaviormentioning
confidence: 81%
“…Mother rats (Rattus norvegicus) approach and maintain proximity to a pup that is emitting cries (ultrasonic vocalizations) significantly more than do virgin rats [25]. This study showed that a warm, silent pup together with recorded ultrasounds was required to elicit approach of maternal or virgin females, the former remaining in proximity of the pup for a significantly longer period of time.…”
Section: Crying and Parental Behaviormentioning
confidence: 81%
“…Thus, the association between locomotor activity and USV may increase maternal attention and care via visual stimuli (Weller & Dubson, 1998), in addition to the already reported role of USVs in modulating maternal behavior (Ehret, 1980;Farrell & Alberts, 2002a,b;Noirot, 1972Noirot, , 1974Sewell, 1970;Smotherman et al, 1974). An additive value of two sensory modalities (viz., the olfactory and acoustic ones) in stimulating the maternal response toward the pup has been described previously (Farrell & Alberts, 2002b;Smotherman et al, 1974). Moreover, pup movements also may enhance sound propagation, favoring detection by the mother.…”
Section: Discussionmentioning
confidence: 95%
“…This distress behaviour is intended to elicit maternal attention and retrieval, as well as to modulate maternal care behaviour by stimulating prolactin production (Noirot, 1972;Hashimoto et al, 2001;Farrell and Alberts, 2002). These distress behaviours can be recorded and analysed both quantitatively and qualitatively in order to measure levels of distress-like behaviour in both infant mice and rats (Groenink et al, 2008;Scattoni et al, 2009).…”
Section: Separation-induced Ultrasonic Vocalizationsmentioning
confidence: 99%